The trends of isolation and antimicrobial susceptibility of group B Streptococcus in urine culture: a 7-years cross sectional study - Kannambath, Rachana; Vasanthaiah, Shruthi; Jamir, Imola; Sagili, Haritha; Mandal, Jharna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Group B Streptococcus (GBS)/Streptococcus agalactiae (S. agalactiae) is a common rectovaginal colonizer, thereby a potential agent of neonatal and maternal infection. This study estimates the trends of isolation of GBS, its antimicrobial profile in urine culture and the demographic characteristics of these patients over a 7-year period. Methods: A record-based study was conducted, which included all the urine culture reports of GBS/S. agalactiae from January 2014 to December 2020. The trend of occurrence of GBS bacteriuria, demographic characteristics and antimicrobial susceptibility pattern were analyzed. Results: Out of 137 urine samples which grew GBS/S. agalactiae, 55(40.15%) were from antenatal women. Most of the isolates were from females (72.26%), with a male preponderance noted among the elderly population (age>60 years). The predominant age group affected were adults between 20 to 59 years. The majority of the isolates (60.58%) were susceptible to all the four tested antibiotics, namely, ciprofloxacin, nitrofurantoin, ampicillin and vancomycin. Ciprofloxacin resistance was observed in 32.85% (45/137) isolates, 5.84% (8/137) isolates were resistant to ampicillin and 2.92% (4/137) were resistant to nitrofurantoin. Conclusions: All the isolates were susceptible to vancomycin. GBS/S. agalactiae is an important agent of bacteriuria in antenatal women as well as in non-pregnant population, especially the elderly males. Emerging resistance to various group of antibiotics warrants routine susceptibility testing.